Changing pattern of resistant pathogens causing urinary tract infections in Karachi - Najmul, H; Tanveer, A (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: The study under view is based under the aim to investigate the prevalence and susceptibility pattern of pathogens, causing urinary tract infections (UTIs), to antibiotics commonly used in routine medication. MATERIALS AND METHODS: Over a period of 10 months 100 isolates were collected for the determination of their susceptibility to chosen antibiotics, from a laboratory (MedPath Laboratories) in urban area of Karachi. All Gramnegative and Gram-positive urinary tract pathogens were re-identified by their morphological and biochemical characteristics and the susceptibility to seven antibiotics was determined. RESULTS: Pathogens were found as, Escherichia coli, Pseudomona spp, Klebsiella species, Enterobacter spp., and Staphylococci spp. In recent study, more than half of the Escherichia coli isolates were resistant to one or more of the all antimicrobial drugs tested. Resistance was most common to amoxicillin/clavulanic acid and ofloxacin, cefixime, followed by gentamicin. Our results indicate that Escherichia coli and Pseudomonas spp. were the most common organisms causing UTI. Other organisms involved were Enterobacter spp., Staphylococcus spp., and Klebsiella spp. Increasing patterns of resistant to gentamicin, and ofloxacin were also observed. CONCLUSIONS: In conclusion, pattern of antibiotic susceptibility to first line antibiotics is changing hence antimicrobial susceptibility testing of all isolates is crucial for the treatment of UTI. DOI: http://dx.doi.org/10.3126/ijim.v2i3.8069 Int J Infect Microbiol 2013;2(3):99-104